PENGARUH PENGUASAAN PENGUKURAN TERHADAP HASIL BELAJAR FISIKA SISWA PADA MATERI BESARAN DAN SATUAN - Sari Wahyuni Rozi Nasution (Jurnal Education and Development, 2019)
The aims of the research is to know general description about measurement mastery and magnitude and units, then to know whether there is a significant effect between measurement mastery toward physics learning outcomes on magnitude and units material at the tenth grade students of SMA Negeri 2 Padangsidimpuan. The research method used is descriptive method. The population is all of the tenth grade students are 232 students. The sample is 38 students which are taken by random sampling technique. The data is collected by using test as an instrument. The writer uses statistic processes in analyzing data. They are descriptive analysis and inferential analysis by using the formula of “r” Product Moment and the formula of t test. After collecting the data, it is found the average of measurement mastery can be categorized “good” . Meanwhile the average of students’ learning outcomes of magnitude and units can be categorized “good”. The result of the analyzed data shows the score of ttest > ttable (2,17 > 1,70) . in other words, the score of ttest is bigger than ttable. So, the hypothesis is accepted. It means there is significant effect of measurement mastery toward students’ learning outcomes of magnitude and units at the tenth grade students of SMA Negeri 2 Padangsidimpuan.